Políticas públicas da educação inclusiva de 1990 a 2009: conquistas e contradições na inclusão de alunos com necessidades educacionais especiais na educação básica - Silva , Catia Alire Rodrigues Arend da (2011)
This dissertation approaches the theme The Public Policies of Inclusive Education directed at Brazilian Education. This is an analysis of the contradictions of public policy from the 1990s to 2009, in addressed two decades, public policies in Brazilian education by the inclusion of students with special needs reveal contradictions between what is proposed and the limits imposed by neoliberal policies. Presents itself as problem to clarify how the school inclusion public policies are implemented in the Brazilian education reality, which factors involve in its definition and what is the ideology that underlies its proposals in the corresponding period from the 1990s. As objective advisors to understand how the Brazilian government has taken legal principles of inclusion from the 1990s; examine national documents that support inclusive policies in education, analyzing the policies of inclusive education in capitalist society (neoliberal) as an achievement the human right to education, performing a critical analysis of posture and actions of the State in the field of public policies, especially in the area of Inclusive Education. The survey was conducted by analysis of the documents formally drawn up within the national territory: the Law of Directives and Bases of National Education LDB 9394/96 and Plan for Development of Education in 2007 as a result of a historically constructed to respond to social concerns. It is presented for analysis of the study object the following categories: exclusion / inclusion, neoliberalism, equality and citizenship. The perspective of historical materialism enables us to understand the contradictions between what is presented by this legal aspect in the analyzed documents and educational practice, between the implementation of public policies and interests inherent in the logic of capital and the way as the students with special educational needs are being included in regular education. The limits and contradictions of neoliberal policies in the perspective of inclusive education explain that the quality of education and citizenship training for individuals with disabilities to delimit the interests of the market.